Assessing student perceptions of academic assignments / Rafizah Kechil and Chew Yee Ming - Kechil, Rafizah; Chew, Yee Ming (Unit Penerbitan JSKM, 2025)
Academic assignments are critical in shaping student learning experiences, providing opportunities to apply theoretical concepts to practical scenarios. This study examines student perceptions of assignments, focusing on their clarity, relevance, and applicability to real-world contexts. A structured Likert-scale survey was employed to assess key factors, including the alignment of assignments with course objectives and their effectiveness in fostering critical thinking and problem-solving skills. The findings reveal the significance of clear instructions and well-defined objectives in enhancing student engagement and learning outcomes. This article offers actionable recommendations for educators to design assignments that bridge the gap between academic learning and practical applications, ensuring students are equipped with the skills needed for future success.